Evaluasi Badan Usaha Milik Desa (BUMDes) Di Desa Pagelaran, Kecamatan Ciomas, Kabupaten Bogor Periode 2015-2018. - Ulul Hidayah; Sri Mulatsih; Yeti Lis Purnamadewi (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
BUMDes is a village development innovation that aims to strengthen the economy of the village community, but its success has not looked good enough in many villages. So this study aims to evaluate the process of forming and implementing BUMDes in Pagelaran Village for 3 years. This research method uses qualitative descriptive analysis. Data were obtained through interviews with selected respondents and BUMDes documents. The results showed that the process of establishing Harapan Jaya BUMDes was in accordance with applicable rules. Although at the beginning of the establishment of the management structure the BUMDes were not in accordance with the rules but had been corrected after one year. The implementation of BUMDes Harapan Jaya 2015-2016 experienced bankruptcy because of the lack of commitment from the management. Afterward, the implementation of Harapan Jaya BUMDes had planned to establish six business units in 2017, yet only four business units could be realized until the end of 2018. These business units have not been able to empower the community and reduce the unemployment rate in Pagelaran Village because the total employments of these business units are only 20 people. BUMDes turnover is good, but the profit obtained is very small so it has not been able to contribute to the Village Original Income.